The application of nursing diagnoses in Intensive Care Units: A scoping review of clinical indicators and patient outcomes - Wahyuni, Erna Dwi; Nursalam, Nursalam; Dewi, Yulis Setiya; Puspitasary, Novalia; Klankhajhon, Sirikanok; Ye, Jia-You; Arifin, Hidayat (Faculty of Nursing Universitas Padjadjaran, 2025)
Introduction: Nursing diagnoses are essential in Intensive Care Units (ICUs) for guiding decisions, prioritizing care, and improving outcomes. However, inconsistent terminology and documentation burdens hinder their effective implementation and evaluation. The aimed of this study was to examine the application of nursing diagnoses in ICUs, exploring their relationships with clinical indicators, patient outcomes, and the impact of standardized diagnostic frameworks on nursing practice. Methods: This scoping review followed PRISMA-ScR guidelines We searched PubMed, CINAHL, Scopus, and Web of Science from 2019 to 2024. Studies examining nursing diagnoses in ICU settings were included. The reviewers independently screened 527 records, with nineteen full-text articles assessed for eligibility, resulting in thirteen included studies. Results: Thirteen studies with diverse methodologies from multiple countries were analyzed. Four key themes emerged: 1) Clinical indicators linked to specific nursing diagnoses, particularly respiratory conditions where impaired spontaneous ventilation was associated with dyspnea, fever, fatigue, and cough; 2) Implementation processes for nursing diagnoses, including electronic health records and nurse-delivered thoracic ultrasound that enhanced clinical decision-making; 3) Diagnostic validation and prevalence studies highlighting the importance of standardized frameworks for accurate diagnosis; and 4) Interventions that improved nursing practice and patient outcomes, including the institutionalization of nursing processes and development of electronic care plans. Conclusion: Standardized nursing diagnoses optimize ICU patient care by providing a structured approach to assessment, intervention planning, and outcome evaluation. Technology integration and consistent terminology enhance diagnostic accuracy and intervention effectiveness. Future research should focus on validating these frameworks across diverse ICU settings and patient populations to establish best practices for implementation.